THE URGENCY OF PROFESSIONALISM IN LIBRARY MANAGEMENT AT PRIMARY SCHOOL - Khasanah, Sovia Nur; Amalia, Nur (UIN Sumatera Utara Medan, 2023)
This study's objective is to explore the role of school library management in enhancing students' academic performance and to identify the barriers to effective library management. It adopts a qualitative research approach, utilizing a case study design. Data was collected through interviews, observations, and document analysis. Data analysis involved three main stages: data reduction, presentation, and drawing conclusions. The findings reveal a lack of professional library management at elementary school Demakan 02 due to the absence of qualified librarians, which has led to the library operating in an ad-hoc manner.